2004
DOI: 10.1111/j.1365-2621.2004.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition and some physical properties of a water‐soluble gum from Prosopis africana seeds

Abstract: A water-soluble gum was extracted from the endocarp capsule of the seed coat of Prosopis africana. The gum yield varied substantially with the method of dehulling. Maximum yield was obtained after boiling in 0.1 m Na 2 CO 3 for 4 h. The effects of two different gum concentrations on the rheological properties of gum solutions were examined. The gum formed viscous solutions at low concentrations and exhibited stable viscosity in the pH range 6.0-8.0. Chemical analyses showed that the purified gum had a composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 16 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Achi and Okolo [28] results demonstrated that the Prosopis africana seed gum had a slight reduction in viscosity affected by addition of 100 mM NaCl. They concluded that salt enhanced flexibility of the molecules, which imposed conformational change that led to a decrease in viscosity.…”
Section: Influence Of Saltsmentioning
confidence: 95%
“…Achi and Okolo [28] results demonstrated that the Prosopis africana seed gum had a slight reduction in viscosity affected by addition of 100 mM NaCl. They concluded that salt enhanced flexibility of the molecules, which imposed conformational change that led to a decrease in viscosity.…”
Section: Influence Of Saltsmentioning
confidence: 95%
“…(Burkart, 1952). A fully water-soluble gum is extracted from the "endocarp capsule" of the seed coating of Prosopis africana (Achi & Okolo, 2004). The extracted gum from P. flexuosa DC seeds had a particular composition, which resembled other commercial gums from the leguminous family, but it contained a high content (66.1-72.5%, w/w) of total polysaccharide.…”
Section: Chemical Namementioning
confidence: 99%
“…It is comprised of two major fractions: (i) an acidstable core glucomannan (43%) with G/M ratio of 10:2, and (ii) a (Achi & Okolo, 2004;Amin, Ahmad, Yin Yin, Yahaya, & Ibrahim, 2007;Amin & Arshad, 2009)-linked xylan (24.29%) including acidic side chains at C-2 and C-3 of the xylosyl residues in the acid-soluble portion. It also contains a minor fragment of glucan (2.31%) as a degraded cellulose material with DP equal to 80 (Anjaneyalu & Channe Gowda, 1979;Razavi et al, 2009;Tharanathan & Anjaneyalu, 1975).…”
Section: Chemical Namementioning
confidence: 99%
See 1 more Smart Citation
“…The maximum viscosity was obtained around the pH 7.0 for BAG solution, where the shape of hydrocolloids chains is close to rod conformational state (Achi & Dkolo, 2004). This condition usually appears at pH values lower than 9, where acid groups are ionized and electrostatic repulsion reaches a maximum and consequently, tends to keep the molecules in an extended form, leading to a high viscous solution and higher k values (Medina- Torres & La Fuente, 2000;Coupland, 2013) The decrease of viscosity from pH 7 to 10 may be explained by the neutralization effect of added alkali on the negative charges of the gum, which reduces the hydrodynamic volume of the gum and consequent viscosity (Chen et al, 2006;Porto et al, 2015) and also gum depolymerization under alkali condition, proposed by Achi & Dkolo (2004).…”
Section: Ph Dependencymentioning
confidence: 99%